EXPLORATION OF LAND RESOURCES FOR ANALYSING THE SUITABILITY OF SELECTED CROPS IN AN ADMINISTRATIVE UNIT OF THRISSUR DISTRICT, KERALA - K. Shyju (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
The fitness of land for a defined use is termed as land suitability. The aim of the study is to find the land suitability of for selected crops examining the indicators of land suitability. The study focuses on analysing suitability of agricultural crops in Pazhayannur Block of Thrissur District. Pazhayannur is the administrative unit (block) in the east of the Talapilli Taluk of Thrissur District in Kerala. The physical and chemical characteristics of the soils of Pazhayannur block like texture, depth, slope, erosion, pH, salinity and soil available primary nutrients (NPK), secondary nutrients and micronutrients are identified. The slope of the terrain using Cartosat-Digital Elevation Model, soil erosion, rainfall and land capability is analysed for suitability classification. Land suitability is studied for the selected crops like paddy, banana, coconut, and rubber. The weighted overlay analysis in GIS is adopted for the analysis. The parameters are weighted based on its class and its influence in suitability of specific crops. The results on agricultural land suitability for individual crops were divided into 5 categories according to the land suitability classification of the United Nations Food and Agriculture Organization (FAO). It is identified that Pazhayannur has potential for the cultivation of the selected crops. The crops show high suitability (S1) in minor proportion and moderate suitability (S2) is found in 30 percent and above and marginal suitability (S3) is noticed in lesser areas. There is few portion of land which is currently not suitable for cultivation (N1) because of its topographic limitations. The restricted areas of forest are permanently not suited for agriculture (N2).